Odpowiedź :
Cześć!
b)
[tex]x\sqrt3-x=3-\sqrt3\\\\x(\sqrt3-1)=3-\sqrt3\\\\x=\frac{3-\sqrt3}{\sqrt3-1}=\frac{3-\sqrt3}{\sqrt3-1}\cdot\frac{\sqrt3+1}{\sqrt3+1}=\frac{3\sqrt3+3-3-\sqrt3}{(\sqrt3)^2-1^2}=\frac{2\sqrt3}{3-1}=\frac{2\sqrt3}{2}\\\\\huge\boxed{x=\sqrt3}[/tex]
c)
[tex]4(x+1)=x(x+4)-(x-2)(x+2)\\\\4x+4=x^2+4x-(x^2-2^2)\\\\4x+4=x^2+4x-(x^2-4)\\\\4x+4=x^2+4x-x^2+4\\\\4x+4=4x+4\\\\4x-4x=4-4\\\\0=0[/tex]
Równanie tożsamościowe, ma nieskończenie wiele rozwiązań.
Odpowiedź:
[tex]b)\\\\x\sqrt{3}-x=3-\sqrt{3}\\\\\sqrt{3}x-x=3-\sqrt{3}\\\\(\sqrt{3}-1)x=3-\sqrt{3}\ \ |:(\sqrt{3}-1)\\\\x=\dfrac{3-\sqrt{3}}{\sqrt{3}-1}\\\\\\x=\dfrac{3-\sqrt{3}}{\sqrt{3}-1}\cdot\dfrac{\sqrt{3}+1}{\sqrt{3}+1}\\\\\\x=\dfrac{(3-\sqrt{3})(\sqrt{3}+1)}{(\sqrt{3}-1)(\sqrt{3}+1)}\\\\\\x=\dfrac{3\sqrt{3}+\not3-\not3-\sqrt{3}}{(\sqrt{3})^2-1^2}\\\\\\x=\dfrac{2\sqrt{3}}{3-1}\\\\\\x=\dfrac{\not2\sqrt{3}}{\not2}\\\\\\x=\sqrt{3}[/tex]
[tex]c)\\\\4(x+1)=x(x+4)-(x-2)(x+2)\\\\4x+4=x^2+4x-(x^2-4)\\\\4x+4=\not x^2+4x-\not x^2+4\\\\4x+4=4x+4\\\\4x-4x=4-4\\\\0=0\\\\R\'ownanie\ \ to\.zsamo\'sciowe\ \ ma\ \ niesko\'nczenie\ \ wiele\ \ rozwiaza\'n\ \ x\in R[/tex]